1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Cubic formula?

  1. Feb 9, 2008 #1
    The quadratic formula is, as you are well aware:

    [tex]ax^2+bx+c=0[/tex] [tex]x=\frac{-b\pm\sqrt{b^2-4ac}}{2a}[/tex]

    What is the cubic formula?


  2. jcsd
  3. Feb 9, 2008 #2
    Cardano's formula will get you one root, but you have to transform the general equation a*x^3+b*x^2+cx+d=0 into e*z^3+f*z+g=0 by use of the substitution z=x-b/3. Mathworld explains a bit more: http://mathworld.wolfram.com/CubicFormula.html
  4. Feb 9, 2008 #3
  5. Feb 9, 2008 #4
  6. Oct 17, 2010 #5
    could someone just show me with an example on how to work the cardano and Del ferro method from start to finish say using x^3-6x^2+2x-1
  7. Oct 17, 2010 #6


    User Avatar
    Science Advisor

    The first thing you do is "reduce" the equation to the form [itex]x^3+ bx= c[/itex] without any [itex]x^2[/itex] term. To do that, let x= y- a. Then [itex]x^3= (y- a)^3= y^3- 3ay^2+ 3a^2y- a^3[/math] and [itex]x^2= (y- a)^2= y^2- 2ay+ a^2[/math]

    [tex]x^3- 6x^2+ 2x-1= y^3 -ay^2+ a^2y- a^3- 6y^2+ 12ay- 6a^2+ 2y- 2a- 1[/tex][tex]= y^3+ (-a- 6)y^2+ (a^2+ 2)y+ (-a^3- 2a- 1)[/math]

    That will have no "[itex]y^2[/itex]" term is a= -6 and, in that case, the polynomial is
    [itex]y^3+ 38y+ 229[/itex] and so our equation is [itex]y^3+ 38y+ 229= 0[/itex].

    Here's a quick review of Cardano's formula:
    [itex](a+ b)^3= a^3+ 3a^2b+ 3ab^2+ b^3[/itex]
    [itex]-3ab(a+ b)= -3a^2b- 3ab^3[/itex]
    so that [itex](a+ b)^3+ 3ab(a+ b)= a^3+ b^3[/itex].

    In particular, if we let x= a+b, m= 3ab, and [itex]n= a^3+ b^3[/itex], [itex]x^3+ mx= n[/itex].

    Can we go the other way? That is, given m and n, can we find a and b and so find x?

    Yes, we can. From [itex]m= 3ab[/itex], we have [itex]b= m/(3a)[/itex] so [itex]a^3+ b^3= a^3+ m^3/(3^2a^3)= n[/itex]. Multiplying through by [itex]a^3[/itex], [itex](a^3)^2+ m^3/3^3= na^3[/itex] or [itex](a^3)^2- na^3+ m^3/3^3= 0[/itex].

    We can think of that as a quadratic equation in [itex]a^3[/itex] and solve it with the quadratic formula:
    [tex]a^3= \frac{n\pm\sqrt{n^2- 4\frac{m^3}{3^3}}}{2}[/itex][itex]= \frac{n}{2}\pm\sqrt{\left(\frac{n}{2}\right)^2- \left(\frac{m}{3}\right)^3}[/tex]
    and a is the cube root of that.

    From [itex]n= a^3+ b^3[/itex] we have
    [tex]b^3= n- a^3= \frac{n}{2}\mp\sqrt{\left(\frac{n}{2}\right)^2- \left(\frac{m}{3}\right)^3}[/tex].

    Now, in this problem, [itex]y^3+ 38y+ 229= 0[/itex] or [itex]y^3+ 38y= -229[/itex] so m= 38 and n= -229.
    [tex]\frac{n}{2}= -\frac{229}{2}[/tex]
    [tex]\left(\frac{n}{2}\right)^2= \frac{52441}{4}[/itex]

    [tex]\frac{m}{3}= \frac{38}{3}[/tex]
    [tex]\left(\frac{m}{3}\right)^3= \frac{54872}{27}[/tex]

    [tex]a^3= -\frac{229}{2}\pm\sqrt{\frac{52441}{4}- \frac{54872}{27}}[/tex]
    [tex]b^3= -\frac{229}{2}\mp\sqrt{\frac{52441}{4}- \frac{54872}{27}}[/tex]

    Calculate those numbers, take the cube roots to find a and b and then find x= a+ b.
    Each of those will have 3 cube roots but in the various ways of combining them, some things will cancel so that there will be, at most, 3 roots to the equation.
  8. Oct 17, 2010 #7
    thank yo for taking the time to show me this but im still confused, after plugging in y-a into the equation how does a= -6
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook